IMPLEMENTASI BIMBINGAN KONSELING DI SEKOLAH DASAR - Rafael Lisinus Ginting (Universitas Negeri Medan, 2020)
Abstract: Implementation of Counseling Guidance in Primary Schools. It is very important to understand about guidance and counseling in elementary schools, especially those relating to the implementation of counseling guidance interventions and school counselor skills in conducting counseling interventions. The purpose of writing this article is to provide understanding to various groups related to the implementation of guidance and counseling in elementary schools. The method used in producing this article is to do a literature review. The results of the literature review regarding the implementation of guidance and counseling in elementary schools are as follows: 1) the implementation of guidance and counseling in elementary schools, 2) education and training for counselors in elementary schools, 3) the skills to do counseling guidance interventions for students, 4) personal characteristics of counselors in elementary schools. This paper is expected to be useful for prospective school counselors to be able to adjust it to the needs of their profession as counselors in elementary schools. Keywords: Counseling Guidance; Skills and Characteristics of Counselors, BK in Elementary Schools Abstrak: Implementasi Bimbingan Konseling Di Sekolah Dasar. Penting sekali untuk memahami tentang bimbingan dan konseling di Sekolah Dasar terutama yang berkaitan dengan pelaksanaan intervensi bimbingan konseling serta keterampilan konselor sekolah dalam melakukan intervensi konseling. Tujuan penulisan artikel ini adalah untuk memberikan pemahaman kepada berbagai kalangan berkaitan dengan implementasi bimbingan dan konseling di Sekolah Dasar. Metode yang dipakai dalam mengghasilkan artikel ini adalah dengan melakukan telaah pustaka. Adapun hasil dari telaah pustaka mengenai implementasi bimbingan dan konseling di Sekolah Dasar adalah sebagai berikut: 1) pelaksanaan bimbingan dan konseling di Sekolah Dasar, 2) pendidikan dan pelatihan bagi konselor di Sekolah Dasar, 3) keterampilan melakukan intervensi bimbingan konseling bagi siswa, 4) karakteristik pribadi konselor di Sekolah Dasar. Tulisan ini diharapkan bermanfaat bagi para calon konselor sekolah untuk dapat menyesuaikannya dengan kebutuhan profesinya sebagai konselor di Sekolah Dasar. Kata kunci: Bimbingan Konseling; Katerampilan dan Karakteristik Konselor, BK di Sekolah Dasar